2010
DOI: 10.3897/zookeys.37.301
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Mesobuthus Vachon, 1950 (Scorpiones, Buthidae) from Xinjiang, China

Abstract: A new species of the genus Mesobuthus Vachon, 1950 is described, based on specimens collected in the northern piedmont of the Tianshan Mountains, Xinjiang. It is characterized by a slender chela, general coloration yellow to pale brownish-yellow, elongate aculeus and 2-4 markedly large and moderately extroversive lobed granules of the ventrolateral carinae of metasoma segment V. With the description of this new species, the number of known Chinese species of Mesobuthus is raised to fi ve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,170 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Kovařík [50] found four lateral eyes for Butheolus species, and pointed out that “the fourth eye” “may possibly be overlooked”. In our study, we found species M. martensii [9], [10], [11], [15], M. caucasicus [11], [15], [16], [17], [51] and M. eupeus with their subspecies [11], [12], [13], [14], [15], [51] were studied numerous of times. Though there was no lack of good descriptions with drawings or high-tech photography among these studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kovařík [50] found four lateral eyes for Butheolus species, and pointed out that “the fourth eye” “may possibly be overlooked”. In our study, we found species M. martensii [9], [10], [11], [15], M. caucasicus [11], [15], [16], [17], [51] and M. eupeus with their subspecies [11], [12], [13], [14], [15], [51] were studied numerous of times. Though there was no lack of good descriptions with drawings or high-tech photography among these studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Though there was no lack of good descriptions with drawings or high-tech photography among these studies, e.g. Qi, et al [10], Sun & Zhu [16], Mirshamsi, et al [14], Sun & Sun [11], these “extra” lateral eyes were also not mentioned. Even the scanning electron microscopy were used in morphological studies, the same case still occurs, for example, Figure 2 of Lourenço & Leguin [26] illustrated a “Five-eye” model, but unfortunately, the No.…”
Section: Discussionmentioning
confidence: 99%
“…Kovar ˇı ´k [50] found four lateral eyes for Butheolus species, and pointed out that ''the fourth eye'' ''may possibly be overlooked''. In our study, we found species M. martensii [9,10,11,15], M. caucasicus [11,15,16,17,51] and M. eupeus with their subspecies [11,12,13,14,15,51] were studied numerous of times. Though there was no lack of good descriptions with drawings or high-tech photography among these studies, e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Though there was no lack of good descriptions with drawings or high-tech photography among these studies, e.g. Qi, et al [10], Sun & Zhu [16], Mirshamsi, et al [14], Sun & Sun [11], these ''extra'' lateral eyes were also not mentioned. Even the scanning electron microscopy were used in morphological studies, the same case still occurs, for example, Figure 2 of Lourenc ¸o & Leguin [26] illustrated a ''Five-eye'' model, but unfortunately, the No.…”
Section: Discussionmentioning
confidence: 99%
“…published the first comprehensive report on scorpions from Xizang, and discovered eight new species belonging to the families Chaerilidae ( Chaerilus ) and Euscorpiidae ( Euscorpiops and Scorpiops ) [ 13 ]. Subsequently, new genera, new species, a new record of genera and species, and re-descriptions were reported continuously [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. At the same time, some revisions on scorpion distribution and taxonomy of the genera were completed [ 16 , 20 , 29 , 30 , 33 , 34 , 35 , 36 ].…”
Section: Scorpion Species From Chinamentioning
confidence: 99%